2002
DOI: 10.1590/s1516-44462002000400005
|View full text |Cite
|
Sign up to set email alerts
|

Validity Study of the South Oaks Gambling Screen (SOGS) among distinct groups of Brazilian gamblers

Abstract: OBJECTIVE: The main objective of this study was to assess the internal consistency and to perform a factor analysis of the Brazilian version of the SOGS - South Oaks Gambling Screen - scale, as well as its ability to discriminate between different profiles of gamblers. METHOD: Two hundred and seventeen subjects were enrolled in the study: 46 gamblers under treatment at the Gamblers Treatment Unit of PROAD - Program for Orientation and Attention of Dependent Persons- of the Federal University of São Paulo; 96 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
9

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
0
7
1
9
Order By: Relevance
“…Although the SOGS has been primarily employed as a screening device to identify problem gamblers, the present study uses the SOGS as an index of gambling severity. Many studies have suggested that whilst most screening instruments have limitations, the SOGS is an appropriate measure in discriminating nonproblem gamblers from problematic gamblers (Oliveira, Silva, & da Silveira, 2002;Weinstock, Whelan, Meyers, & McCausland, 2007).…”
Section: Design and Materialsmentioning
confidence: 99%
“…Although the SOGS has been primarily employed as a screening device to identify problem gamblers, the present study uses the SOGS as an index of gambling severity. Many studies have suggested that whilst most screening instruments have limitations, the SOGS is an appropriate measure in discriminating nonproblem gamblers from problematic gamblers (Oliveira, Silva, & da Silveira, 2002;Weinstock, Whelan, Meyers, & McCausland, 2007).…”
Section: Design and Materialsmentioning
confidence: 99%
“…We did not assume the opposite, i.e. traits differentiating PG from controls as necessarily impulsive since the true nature of PG (impulsive, compulsive, or else) Gambling Screen (SOGS) [30][31] and Section 5 of the Schedules for Clinical Assessment in Neuropsychiatry (SCAN) 32 were used for further diagnostic confirmation. Patients with psychotic symptoms were excluded.…”
Section: Par T 2 1) Subjectsmentioning
confidence: 99%
“…Essa escala foi validada e adaptada para a população brasileira por Oliveira et al 21 , com o objetivo de discriminar jogadores patológicos de jogadores não patológicos, como também diferenciar grupos clínicos de não clínicos e identificar graus distintos de gravidade do hábito de jogar (jogador patológico, jogador social e não tem problemas com o hábito de jogar). A escala original tem 20 itens, e 5 é o ponto de corte para avaliar se a pessoa é um provável jogador patológico.…”
Section: Instrumentosunclassified